2019
DOI: 10.4143/crt.2018.575
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Regional Nodal Irradiation for Breast Cancer Patients with Supraclavicular and/or Internal Mammary Lymph Node Involvement: A Multicenter, Retrospective Study (KROG 16-14)

Abstract: PurposeThe purpose of this study was to evaluate the treatment outcomes of radiotherapy (RT) for breast cancer with ipsilateral supraclavicular (SCL) and/or internal mammary (IMN) lymph node involvement.Materials and MethodsA total of 353 patients from 11 institutions were included. One hundred and thirty-six patients had SCL involvement, 148 had IMN involvement, and 69 had both. All patients received neoadjuvant systemic therapy followed by breast-conserving surgery or mastectomy, and postoperative RT to whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…28 And a multicenter study of 353 patients from South Korea showed that high-dose RT did not translate into survival benefits. 11 These were also consistent with our preliminary study results of radiation dose.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…28 And a multicenter study of 353 patients from South Korea showed that high-dose RT did not translate into survival benefits. 11 These were also consistent with our preliminary study results of radiation dose.…”
Section: Discussionsupporting
confidence: 92%
“…These findings supported that combined therapy can improve the survival outcomes of mISLM patients and were in agreement with those of current mainstream studies. [9][10][11][12] Additionally, we found in the multivariate analyses that the pN3 stage was an important factor affecting PFS. This indicated that ISLM patients with pN3 stage had a higher risk of supraclavicular lymph node failure and were more likely to develop disease progression, which was also consistent with the previous results of Fan et al And this may be related to the micrometastasis of tumor cells in supraclavicular vessels.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In their study, Aleknavičius et al found that IMN-RT was correlated with a better survival outcome for patients with moderate-risk disease (stage T1-2N1), and showed no association for better survival for high-risk disease (stage T3-4N2-3) (18). In their study, Kim et al reported that IMN-RT was not associated with DFS in IMN patients (19). The result of our study was largely consistent with the findings of the abovementioned clinical retrospective studies; inferior results of the innerquadrant tumors were more prominent for patients with a better survival prognosis.…”
Section: Discussionmentioning
confidence: 94%
“…[4][5][6] Despite the possibility of over-diagnosis, more patients with SCN and/or IMN involvement are referred for RT, but there is a paucity of data regarding the outcomes for these patients. Neoadjuvant chemotherapy is usually administered to these patients [7][8][9] ; however, upfront surgery can also be a viable option at the discretion of the attending surgeons. 10,11 In particular, in the upfront surgery setting, SCN excision can be performed along with breast surgery during the same operation; however, the benefit of aggressive regional therapy is controversial.…”
Section: Introductionmentioning
confidence: 99%